A review of new directions in managing fruit and vegetable processing by-products. (June 2019) - Majerska, Joanna; Michalska, Anna; Figiel, Adam
Abstract: The outer layers of fruit and vegetables are rich in various bioactive compounds, thus being a potentially valuable component of the human diet. But despite the knowledge of its health-promoting properties, fruit and vegetable pomace has not yet been widely used in food industry. Recent years have seen progress in the research on the content of polyphenolic compounds in fruit and vegetable processing by-products, extracting bioactive compounds from fruit and vegetable pomace and studying their impact on human body. This is due to the growing interest in an active and healthy lifestyle and the resulting increased market demand for natural foods. Fruit and vegetable pomace offers strong potential as a functional additive to many food products. The wide range and abundance of natural components in pomace makes it worth investigating in terms of its use on industrial scale. This would help limit the disposal of this valuable raw material and reduce the use of artificial food additives by replacing them with natural additives contained in pomace. The use of pomace components could also reduce the incidence of diseases of affluence or cancerous diseases. This work discusses the current ways and directions in managing fruit and vegetable pomace and presents the forms in which they can be added to food products to enrich them in natural bioactive compounds and nutrients. It also focuses on how the addition of pomace to different food products influences their physical, chemical and sensory properties. Last but not least, the work presents options and methods of using fruit and vegetable pomace in food industry. Highlights: Fruit and vegetable pomace as a by-product has gained a special attention. The newest trends in managing fruit and vegetable pomace are characterized. The current developments in pomace utilisation have been indicated.